Dear Mr. Henshaw - Cleary, Beverly; Zelinsky, Paul O. (New York : Morrow Junior Books, 1983)
In his letters to his favorite author, ten-year-old Leigh reveals his problems in coping with his parents' divorce, being the new boy in school, and generally finding his own place in the world.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
Elem. School Library Collection, June 2000.
Horn Book, January 1996.
L.A. Recommended Foreign Language, February 1999.
4.9.
Keywords: Divorce -- Fiction; Parent and child -- Fiction; Schools -- Fiction; Letters -- Fiction; Books and reading -- Fiction; Newbery medal winner